KUALITAS KEBUN BIBIT MOJOLANGU SEBAGAI RUANG PUBLIK BERDASARKAN PERSEPSI PENGUNJUNG - ichsan, muhammad fatih (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
City parks are green open spaces that have ecological, socio-economic and architectural roles and functions. City parks are also public spaces that have the role of providing comfortable, safe and pleasurable social spaces for all groups. Kebun Bibit Mojolangu is the second largest city park in Malang City with an area of 18,050 square meters with a service capacity of up to 66 thousand visitors. Even though it has a large capacity, it is known that visits to Kebun Bibit Mojolangu are relatively low compared to other parks. The low number of visits and the deficient layout of the park raise question about the quality of Kebun Bibit Mojolangu as a public space based on visitors' perceptions. The purpose is to evaluate the quality of Kebun Bibit Mojolangu as a public space based on visitor perceptions. The methods used in this research are mean score, factor analysis and regression. From the results of the analysis it is known that there are indicator of Community, Pedestrian Connections, Facility Conditions, Visibility, Security Systems, Climate Comfort, Availability of Seating and Layout which take effect the Quality of Kebun Bibit Mojolangu by 0.499 per unit of park quality.